HISTORY OF THE DEVELOPMENT OF LEGAL FORMS OF PROVIDING THE REGIME OF SPACE ACTIVITY - Obikhod, Tetiana; Bilenchuk, Petro (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to determine the specifics of the development of the legal component of space activity in Ukraine and beyond and the trends of its modernization in the context of the future development of the space industry. Methods: the method of historical and legal analysis was used, outlining the prerequisites for the formation and peculiarities of the development of space law in Ukraine; using the methods of analysis and synthesis, the relationship between the goals, functions, and technologies of the modern legal component of the space industry is determined. Results: the problem of the formation and development of the modern legal form of space activity, the development of technologies and scientific approaches to the future of the space industry is updated, the historical and legal aspects of both international space law and space law in Ukraine are outlined; the need for environmental safety in the conditions of the development of space activities is emphasized; the issue of the development of private space initiatives was raised. Discussion: components of a comprehensive approach to the regulation of space activities in international law and the law of Ukraine, the formation of a rethinking of the approach to space activities in the conditions of rapid development of scientific, technological and political components in the civilized world. The development of astronautics has led to the need for legal regulation of space activities both, individually for Ukraine and at the international level in order to meet the needs of studying and developing the resources of space objects and preventing man-made disasters. International legal norms governing human activity in space began to emerge shortly after the launch of the first satellite: October 10, 1967, when the Agreement on the Principles of the Activities of States Regarding the Study and Use of Space, Including the Moon and Other Celestial Bodies appeared; In 1972, the Convention on International Liability for Damage Caused by Space Objects; In 1976, the Convention on Registration of Objects Launched into Space. The area of space development is also regulated by internal law, which applies only to persons under the jurisdiction of the respective state. As an example, the law of Ukraine "On Space Activities" can be presented. Ukraine’s space activities are carried out on the basis of the National Targeted Scientific and Technical Space Program of Ukraine, which is developed for five years and approved by the Verkhovna Rada of Ukraine upon submission of the Cabinet of Ministers of Ukraine. According to the Law of Ukraine "On Amendments to Certain Laws of Ukraine Regarding the State Regulation of Space Activities" No. 143-IX, subjects of space activities can be enterprises, institutions and organizations of any form of ownership and organizational legal form. State policy in the field of space activities is regulated by the Concept of implementation of state policy in the field of space activities for the period until 2032. The main directions of the Concept are related to the improvement of rocket and space technology, the development of space technologies, increasing the scientific and technical potential of the state, commercialization and deepening of international cooperation. In the context of the development of international cooperation in the space sphere, the issue of modernization of the domestic legal system in the space sphere becomes urgent; updating and creating a modern regulatory framework; development of the scientific potential of our country; creation of an information and resource base, a material and technical base for the development of not only the public sector, but also for the support of enterprises, institutions and organizations of any form of ownership for further testing and launch of launch vehicles in outer space. International cooperation with the leaders of the space industry, first of all, with the USA, for the development of its own scientific and technological potential, is promising. Particular attention should be paid to the implementation of the norms of environmental law regarding the preservation of the environment from man-made disasters.